Quality Career Counselling Services: A Developmental Tool for Organizational Accountability - Bezanson, Lynne; Riddle, Dorothy I. (Canadian Journal of Counselling and Psychotherapy, 2007)
There is growing attention to issues concerning quality services in career counselling. At the same time, very few practical working tools are available to help organizations build quality of service principles, practices and policies into all levels of their organizations. Even fewer do so with attention to the importance of staff development as well as quality control as central to quality service. A workbook supporting both objectives has been developed and tested. Its several components are described and a more detailed discussion of an accountability framework is included. The development of additional practical resources to support increased evaluation in career counselling is suggested.